Arlanpa / Diseinua nagusia, Sam Reid, Carl Wieman, Wendy Adams... [et al.] ; itzulpena, José Manuel López Irastorza - Reid, Sam; Wieman, Carl; Adams, Wendy; López Irastorza, José Manuel (; PhET Interactive Simulations, 2012)
Indarra, energia, lana lantzeko simulazio interaktiboa